2015
DOI: 10.1016/j.fertnstert.2015.02.035
|View full text |Cite
|
Sign up to set email alerts
|

Poor ovarian response in women undergoing in vitro fertilization is associated with altered microRNA expression in cumulus cells

Abstract: Objective Micro RNAs (miRNAs) are a large family of short (∼21-nucleotide) non-coding mRNAs that repress gene expression through degradation of target mRNAs and/or inhibition of their translation. In the mouse, miRNAs play a key role in cumulus cell function and miR-21 is implicated in the regulation of cumulus cell viability. In this study, we asked whether miRNA expression is associated with the number of oocytes retrieved in women undergoing IVF and aimed to identify candidate miRNAs that may play a role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 27 publications
1
40
0
1
Order By: Relevance
“…To eliminate potential bias introduced by unequal distribution of samples from patients undergoing either IVF or ICSI, each group consisted of granulosa cell samples isolated from both IVF patients and ICSI patients (Table ). Similar numbers of samples, or fewer, have been reported previously for comparing miRNAs between control and test sample groups (Assou et al, ; Cheng et al, ; Karakaya et al, ; Liu et al, ; Rizzo et al, ). Using the mean expression value of all expressed miRNAs in a given sample as a normalization factor (Mestdagh et al, ) and designating Group 1—BLAST as the control group, we identified 14 miRNAs and one snoRNA that were differentially expressed between the BLAST and FERT groups (Figure and Supplementary Information file 1).…”
Section: Resultssupporting
confidence: 72%
“…To eliminate potential bias introduced by unequal distribution of samples from patients undergoing either IVF or ICSI, each group consisted of granulosa cell samples isolated from both IVF patients and ICSI patients (Table ). Similar numbers of samples, or fewer, have been reported previously for comparing miRNAs between control and test sample groups (Assou et al, ; Cheng et al, ; Karakaya et al, ; Liu et al, ; Rizzo et al, ). Using the mean expression value of all expressed miRNAs in a given sample as a normalization factor (Mestdagh et al, ) and designating Group 1—BLAST as the control group, we identified 14 miRNAs and one snoRNA that were differentially expressed between the BLAST and FERT groups (Figure and Supplementary Information file 1).…”
Section: Resultssupporting
confidence: 72%
“…Some studies have also described altered miRNA expression in patients with ovarian dysfunctions, such as polycystic ovarian syndrome (Sang et al ., 2013; Roth et al ., 2014) and premature ovarian failure (Yang et al ., 2012). Moreover, poor response to controlled ovarian stimulation has also been related to altered miRNA expression (Karakaya et al ., 2015). …”
Section: Discussionmentioning
confidence: 99%
“…As mentioned before, the Pi3k/Akt pathway component genes are highly regulated when evaluated by RNASeq in the ovaries of the same df/df and N mice [20]. Additionally, miR-21-5p was up-regulated in cumulus cells from oocytes of poor-responder older women undergoing IVF procedures [53], indicating that the down-regulation of miR-21-5p observed in df/df mice can be also associated to increased fertility potential.…”
Section: Discussionmentioning
confidence: 99%